Functional regulation of syntaxin-1: An underlying mechanism mediating exocytosis in neuroendocrine cells - Yang, Xinquan; Tu, Weifeng; Gao, Xuzhu; Zhang, Qi; Guan, Jinping; Zhang, Junlong (Frontiers in Endocrinology, 2023)
The fusion of the secretory vesicle with the plasma membrane requires the assembly of soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) protein complexes formed by synaptobrevin, syntaxin-1, and SNAP-25. Within the pathway leading to exocytosis, the transitions between the “open” and “closed” conformations of syntaxin-1 function as a switch for the fusion of vesicles with the plasma membranes; rapid assembly and disassembly of syntaxin-1 clusters on the plasma membrane provide docking and fusion sites for secretory vesicles in neuroendocrine cells; and the fully zippered trans-SNARE complex, which requires the orderly, rapid and accurate binding of syntaxin-1 to other SNARE proteins, play key roles in triggering fusion. All of these reactions that affect exocytosis under physiological conditions are tightly regulated by multiple factors. Here, we review the current evidence for the involvement of syntaxin-1 in the mechanism of neuroendocrine cell exocytosis, discuss the roles of multiple factors such as proteins, lipids, protein kinases, drugs, and toxins in SNARE complex-mediated membrane fusion, and present an overview of syntaxin-1 mutation-associated diseases with a view to developing novel mechanistic therapeutic targets for the treatment of neuroendocrine disorders.